A Semantic Analysis of Promotional Diction in Legislative Candidates’ Campaign Billboards in Malang Raya - M. Isnaini (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The development of mass media and the intensity of political campaigns ahead of the 2024 election encourage the use of billboards as a strategic outdoor communication medium, especially in the Greater Malang area. In this context, the selection of promotional diction is an important aspect because it plays a role in building image, legitimacy, and political persuasion. This study aims to identify the form of promotional diction and explain the function of the language used in billboards of legislative candidates in Malang Raya. The research uses a qualitative descriptive approach with semantic studies. Data in the form of promotional words and phrases were obtained through observation and documentation of 68 candidate billboards, then analyzed using the Miles and Huberman interactive model through the stages of reduction, presentation, and drawing conclusions. The results of the study show that the dominant form of diction includes jargon, foreign words, and abstract words. Jargon is used to build institutional legitimacy, foreign words to create a modern and professional impression, and abstract words to build moral and emotional imagery. The language functions found include persuasive functions in terms of listeners, social contact functions, speech topic functions, and mandate functions. These findings show that promotional diction on candidate billboards is a planned semantic strategy in shaping voters' perceptions and preferences in local public spaces.